Children's Sensitivity to Ulterior Motives When Evaluating Prosocial Behavior. (24th September 2013) - Heyman, Gail; Barner, David; Heumann, Jennifer; Schenck, Lauren
Abstract Reasoning about ulterior motives was investigated among children ages 6–10 years (total N = 119). In each of two studies, participants were told about children who offered gifts to peers who needed help. Each giver chose to present a gift in either a public setting, which is consistent with having an ulterior motive to enhance one's reputation, or in a private setting, which is not consistent with having an ulterior motive. In each study, the 6‐ to 7‐year olds showed no evidence of understanding that the public givers might have ulterior motives, but the 8‐ to 10‐year olds rated the private givers more favorably. In 3., the older children were more likely than the younger children to refer to impression management when explaining their judgments of the givers. The younger children who mentioned impression management did so to justify a preference for public givers (e.g., by explaining that public givers are nicer because more of their peers will know that they are nice). Results from 4. suggest that developmental change in children's reasoning about intentions and social outcomes contributes to their understanding of ulterior motives.